(untitled) (Al-Academy, 2022)
The current research dealt with (the deliberative dimension of the visual sign in the contemporary Iraqi poster) in an attempt to identify the importance of the contemporary poster and the role of the international dimension of the visual sign of exceptional importance.What is the international dimension of the visual mark?- What is the effect of the visual label on the contemporary Iraqi poster? The current research aims to identify the pragmatic dimension in the contemporary Iraqi poster.Across the temporal and spatial research boundaries of the year (2000-2020) in Iraq. The limits of the objective research The limits of this study on the pragmatics in the visual sign and the determination of the relationship between them and its dimensions in the Iraqi poster.As for the second chapter, the theoretical framework and previous studies, the research included two topics:- The first topic (approaches of the deliberative dimension in the visual sign).The second topic (the aesthetics of the contemporary poster). As for the third chapter represented by the research procedures, the researcher followed the descriptive approach in the style of content analysis to achieve the objectives of the research. The research community included a group of contemporary posters obtained by the researcher through the Internet. The current research community reached 12 models. The research sample was intentionally selected according to a set of justifications. The research sample consisted of 5 modelsAs for the fourth chapter, it included the results of the research that the researcher reached through her analysis of the research sample models, the most important of which are:1- The artworks presented a pragmatic dimension of the visual sign in various cases and methods of presentation as in all models.2- The visual sign appears in a symbolic design style in order to achieve its deliberative purpose, as in all models.As for the conclusions:The diversity of showing the structure of the international dimension of the visual sign in1- contemporary times.The design structure contained the international dimension of the visual mark in contemporary times2- and a function with a marketing purposeThe researcher recommended:The researcher recommends encouraging graduate students to investigate the functional concepts of the visual sign and its effective role in society and in contemporary Iraqi painting.The researcher suggested conducting a complementary study to her current research: The Visual Sign and its Deliberative Dimension in the Contemporary World.The research concluded with sources and appendices